Tanggung Jawab Sosial-Yuridis Kepolisian dalam Penegakan Hukum: Studi Kasus Kesalahan Tangkap - Prabandani, Hendra Wahanu; Alwityas, Muhammad Rafliyo Reza; Setiawan, Ichwan; Tejamukti, Robby (HUMANIORUM, 2024)
The criminal justice system has a crucial responsibility in conducting thorough investigations with an emphasis on gathering strong evidence and facts to determine the guilt of individuals in criminal cases and ensure that the convict is given the due rights. The criminal justice process in Indonesia begins with the investigation stage, which involves a series of investigative actions to uncover criminal acts. Investigators can make arrests if there is sufficient initial evidence. However, it is important to understand that the power of arrest must be regulated by law and must not be abused. This research adopts a qualitative approach with a focus on normative law. Data was collected through documents, interviews and observations. The aim of this research is to evaluate the legal structure, basic principles, related regulations, and their application in real situations. The research results show that arrest is an action that involves temporarily detaining a suspect or defendant if there is sufficient evidence for the purposes of investigation and prosecution. Wrongful arrests can occur due to individual identification errors. Wrongful arrest reflects weaknesses in the legal system and can harm wrongly arrested individuals. Victims of wrongful arrest have the right to compensation and rehabilitation in accordance with applicable law.